INNOVATIVE METHODS OF INVOLVING STUDENTS IN RESEARCH ACTIVITIES BASED ON STEAM METHODOLOGY - Kodirov Alijon Abdumannonovich,; G'iyosiddinov Ayubxon Akmalivich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The article analyzes innovative methods of involving students in research activities based on the STEAM educational model. The purpose of the research is to substantiate the effectiveness of the STEAM approach in developing students' scientific and creative abilities and to develop mechanisms for its integration into the educational process. Theoretical analysis, observation, experimental testing, comparison of international experience, and pedagogical diagnostics were used as methodologies. The results show that STEAM-based project and research methods significantly increase students' analytical thinking, use of experience, systematic problem solving, creative thinking and innovative approaches. At the end of the article, practical proposals are given for the implementation of the STEAM system for education in Uzbekistan.